2017
DOI: 10.1002/jcb.26107
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA lncARSR Promotes Doxorubicin Resistance in Hepatocellular Carcinoma via Modulating PTEN‐PI3K/Akt Pathway

Abstract: Hepatocellular carcinoma (HCC) is generally resistant to chemotherapy due to intrinsic or acquired drug resistances. Many molecules and signaling pathways are involved in chemo-resistance of HCC cells. However, the contribution of long noncoding RNA (lncRNA) to chemo-resistance of HCC cells is still largely unknown. In this study, we revealed the critical roles of long noncoding RNA lncARSR in chemo-resistance of HCC cells. lncARSR is upregulated in HCC, associated with large tumor size and advanced BCLC stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 41 publications
4
89
0
Order By: Relevance
“…Recent advances regarding genomes have demonstrated that lncRNAs could regulate various critical pathophysiological processes, such as cell proliferation, cell migration, and metastasis within cancers . It was also demonstrated that lncRNAs counted much in modifying the chemo‐sensitivity, for instance, up‐regulated lncRNA lncARSR was observed to promote doxorubicin resistance in HCC via modulating PTEN‐PI3K/Akt pathway . Of note, lncRNA H19, a paternally imprinted gene located in 11p15.5, was increasingly found to be over‐expressed within various cancers, including HCC, glioblastoma, gallbladder cancer, gastric cancer, and so on .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances regarding genomes have demonstrated that lncRNAs could regulate various critical pathophysiological processes, such as cell proliferation, cell migration, and metastasis within cancers . It was also demonstrated that lncRNAs counted much in modifying the chemo‐sensitivity, for instance, up‐regulated lncRNA lncARSR was observed to promote doxorubicin resistance in HCC via modulating PTEN‐PI3K/Akt pathway . Of note, lncRNA H19, a paternally imprinted gene located in 11p15.5, was increasingly found to be over‐expressed within various cancers, including HCC, glioblastoma, gallbladder cancer, gastric cancer, and so on .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It was also demonstrated that lncRNAs counted much in modifying the chemo-sensitivity, for instance, up-regulated lncRNA lncARSR was observed to promote doxorubicin resistance in HCC via modulating PTEN-PI3K/Akt pathway. 10 Of note, lncRNA H19, a paternally imprinted gene located in 11p15.5, was increasingly found to be over-expressed within various cancers, including HCC, glioblastoma, gallbladder cancer, gastric cancer, and so on. [11][12][13][14] To be specific, inhibition of lncRNA H19 and miR-675 expression may promote migration and invasion of HCC cells though AKT/GSK-3β/Cdc25A signaling pathways.…”
mentioning
confidence: 99%
“…For instance, lncRNA MEG3 regulated hepatic lipid mechanism through AKT-mTOR signalling pathway [20] . Long noncoding RNA lncARSR was found to promote hepatic lipogenesis via Akt/SREBP-1c pathway and contribute to the pathogenesis of nonalcoholic steatohepatitis [18] . LncRNA SRA was reported to promote hepatic steatosis through repressing the expression of ATGL [19] .…”
Section: Suppression Of Gm12664 Expression Decreased Ffa-induced Trigmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of transcripts with lengths greater than 200 nucleotides and act as guides, scaffolds, decoys and tethers of other biological molecules which are involved in various biological processes [12][13][14] . In recent years, emerging evidence has revealed that LncRNAs act as important regulators during the pathophysiology of NAFLD [15][16][17][18][19] . Long noncoding RNA lncARSR was found to promote hepatic lipogenesis via Akt/SREBP-1c pathway and contribute to the pathogenesis of nonalcoholic steatohepatitis [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation